2011
DOI: 10.1007/s12010-011-9197-z
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Stable Digestive Alkaline Proteinases from Striped Seabream (Lithognathus mormyrus) Viscera: Characteristics, Application in the Deproteinization of Shrimp Waste, and Evaluation in Laundry Commercial Detergents

Abstract: Alkaline proteases from the viscera of the striped seabream (Lithognathus mormyrus) were extracted and characterized. Interestingly, the crude enzyme was active over a wide range of pH from 6.0 to 11.0, with an optimum pH at the range of 8.0-10.0. In addition, the crude protease was stable over a broad pH range (5.0-12.0). The optimum temperature for enzyme activity was 50 °C. The crude alkaline proteases showed stability towards various surfactants and bleach agents and compatibility with some commercial dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The inhibition caused by this ion suggests the relevance of sulfhydryl residues for the catalytic action of most proteases [24]. The effects of Cu 2+ and Mn 2+ (respectively, 71% and 78%) proved to be similar to those recorded for L. mormyrus enzyme (respectively, 82% and 69%) [25] …”
Section: Effect Of Temperature On Protease Activity and Stabilitysupporting
confidence: 54%
See 1 more Smart Citation
“…The inhibition caused by this ion suggests the relevance of sulfhydryl residues for the catalytic action of most proteases [24]. The effects of Cu 2+ and Mn 2+ (respectively, 71% and 78%) proved to be similar to those recorded for L. mormyrus enzyme (respectively, 82% and 69%) [25] …”
Section: Effect Of Temperature On Protease Activity and Stabilitysupporting
confidence: 54%
“…El-Hadj Ali et al [25] showed that the half-lives of L. mormyrus proteases were about 18 and 17 days in the presence of methanol and acetone, respectively. Interestingly, the stability of the crude protease was highly enhanced by DMSO, DMF, diethyl ether and hexane; the half-lives of the enzyme in the presence of these solvents were more than 30 days.…”
Section: Effect Of Organic Solvents On Enzyme Activity and Stabilitymentioning
confidence: 99%
“…The inhibition caused by this ion suggests the relevance of sulfhydryl residues for the catalytic action of most proteases (Bezerra et al 2005). The effects of Cu 2+ and Mn 2+ (respectively, 4 % and 37.5 %) proved to be stronger than those recorded for L. mormyrus enzyme (respectively, 82 % and 69 %) (El-Hadj Ali et al 2011 …”
Section: Effect Of Temperature On Protease Activity and Stabilitymentioning
confidence: 86%
“…Today, there is an increasing demand for fish proteolytic enzymes. In fact, fish viscera, one of the most important by-products of fishing industry, is known to be an important source of enzymes that can be used for several industrial applications, due to their unique properties, including high activity over a wide range of pH and temperature conditions (Jellouli et al, 2009;El Hadj-Ali et al, 2011;Nasri et al, 2012) and high activity at relatively low concentration (Haard, 1998). Considering the specific characteristics of these enzymes, fish processing by-products are currently used for enzyme extraction.…”
Section: Introductionmentioning
confidence: 99%